Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1097/ajp.0000000000000728
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Causal Mechanisms of Symptom Recovery in Chronic Whiplash-associated Disorders Using Bayesian Networks

Abstract: Objectives: The present study's objective is to understand the causal mechanisms underpinning the recovery of individuals with whiplash-associated disorders (WAD). We applied Bayesian Networks (BN) to answer two study aims: 1) to identify the causal mechanism(s) of recovery underpinning neck-specific exercise, and 2) quantify if the cyclical pathway of the fear avoidance model (FAM) is supported by the present data. Methods: We analysed a prospective cohort dataset of 216 individuals with chronic WAD. Fifteen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 74 publications
1
11
1
1
Order By: Relevance
“…Abbreviation: Suffix with "_3", variables at 3rd month follow-up; Suffix with "_6", variables at 6th month follow-up; Suffix with "_12", variables at 12th month follow-up; Anx, Hospital Anxiety and Depression Scale, anxiety sub-score; Dep, Hospital Anxiety and Depression Scale, depression sub-score; SES, self-efficacy scale score; PCS, pain catastrophizing scale score; NDI, neck disability index; NST, Neck-Specific Training; PPA, Prescribed Physical Activity In contrast to the present finding, a study on chronic whiplash associated disorders (WAD) using BNs reported that selfefficacy partially mediated the greater effect a neck-specific training had on neck pain intensity compared to a general physical activity program (Liew et al, 2019). The different findings between the present study and Liew et al (2019) occurred despite both studies incorporating similar cognitive behavioural components into the neck-specific training programs (Dedering et al, 2014;Peolsson et al, 2014). This suggests that the same training program may have different mechanism of action in different musculoskeletal disorders affecting the same spinal region.…”
Section: F I G U R Econtrasting
confidence: 99%
See 2 more Smart Citations
“…Abbreviation: Suffix with "_3", variables at 3rd month follow-up; Suffix with "_6", variables at 6th month follow-up; Suffix with "_12", variables at 12th month follow-up; Anx, Hospital Anxiety and Depression Scale, anxiety sub-score; Dep, Hospital Anxiety and Depression Scale, depression sub-score; SES, self-efficacy scale score; PCS, pain catastrophizing scale score; NDI, neck disability index; NST, Neck-Specific Training; PPA, Prescribed Physical Activity In contrast to the present finding, a study on chronic whiplash associated disorders (WAD) using BNs reported that selfefficacy partially mediated the greater effect a neck-specific training had on neck pain intensity compared to a general physical activity program (Liew et al, 2019). The different findings between the present study and Liew et al (2019) occurred despite both studies incorporating similar cognitive behavioural components into the neck-specific training programs (Dedering et al, 2014;Peolsson et al, 2014). This suggests that the same training program may have different mechanism of action in different musculoskeletal disorders affecting the same spinal region.…”
Section: F I G U R Econtrasting
confidence: 99%
“…There is some evidence that changes in self-efficacy is a mechanism by which ACT positively influenced the outcome of disability in a heterogeneous cohort of individuals with musculoskeletal pain disorders (Craner et al, 2020), although it is inconsistent (Wicksell et al, 2010). Independent studies from a heterogeneous group of individuals with musculoskeletal pain disorders have identified self-efficacy as an important mechanism driving recovery (Fordham et al, 2017;Liew et al, ,2019Liew et al, , , 2020Mansell et al, 2016;O'Neill et al, 2020;Sherman et al, 2013). Given its importance, it may be prudent to speculate on the reasons underpinning the importance of self-efficacy as a mediator.…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation
“…BN may therefore reveal new relationships that have not been previously hypothesised. BN have previously been used to determine recovery pathways for some musculoskeletal disorders including whiplash [ 22 ] and postoperative cervical radiculopathy [ 23 ], but not for individuals with LBP.…”
Section: Introductionmentioning
confidence: 99%
“…Self-reported pain and neck-related disability which affect personal care, lifting, reading, work, driving, and recreation can predict recovery after whiplash injury (12), but the relations between physical capacity and neck pain and disability are inconclusive (13,14). Improved neck muscle endurance was an important factor in decreasing neck pain in WAD (15). Decreased cervical range of motion can affect daily activities, for example can skill driving be restricted by less than 40° cervical rotation (16).…”
Section: Introductionmentioning
confidence: 99%